Le détour par soi - Christian Jouhaud (L'Atelier du CRH)
In his work, Daniel Fabre uses his autobiographical experience both as a resource and as a watermark. In his book Bataille à Lascaux. Comment l’art préhistorique apparut aux enfants, this experience runs all through his research career and his writing. The detour he made via himself involved both George Bataille’s work – for whom the interpretation of the wall paintings of Lascaux cannot be separate from the experience of their discovering – and the work of Bataille’s analyst. Such a detour enables Daniel Fabre to cross several levels –  from an ethnology of prehistoric or even Marian appearances to children, to an anthropology of symbolics and an anthropology of knowledge about the birth of human being.